Effects Bacterial Inoculation and organic Fertilization on Some Soil Properties and Growth oF Potato Crop Role in Sustainable Agriculture - Haider A. Al-Maamori (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ)
A field experiment was carried out at the Agricultural Research Station in Wasit Governorate, with a design of RCBD this study aimed to determine the role of Bacillus, Azotobacter, and organic fertilizers on soil biological and chemical properties and potato growth indicators. The results of the application experiment showed that the mixed treatment with Azotobacter chroococcum  +   Bacillus megaterium bacteria was superior in terms of the number of Bacillus bacteria in the soil, the number of Azotobacter bacteria in the soil, the soil pH, the leaf area, the tuber weight,and the yield per plant (7.48×106, 8.42×106 cfu, 7.03, 1.92%, 13416 cm2, 129.10 gm, respectively). The organic fertilizer vermicompost was also superior in terms of the number of Bacillus bacteria in the soil, the number of Azotobacter bacteria in the soil, the soil reactivity, the leaf area, the tuber weight, and the yield per plant (4.45×106, 5.58×106, 7.05, 1.92%, 13434 cm2, 136.90 gm, 1386.7 gm, respectively).